Integration of Tetraselmis chuii and Artemia sp. Culture in Industrial-Scale Salt Production - Alamsjah, Mochammad Amin; Islamiyah, Himnna Sayyidatul; Rahmawati, Ghishella Ayu; Putri, Fadhilah Atika; Amalia, Rizka Sandra; Triningtyas, Putranti Hikmah; Pujiastuti, Dwi Yuli; Md Nor, Adibi Rahiman bin (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract The common technique of traditional salt production in Indonesia is seawater evaporation technology, which uses sunlight to produce salt crystals from seawater. However, in general, the applied technology only produces salt with about 80% NaCl and water contents >7%, impurities >2%, and other contaminants. This produced salt is not suitable to be used as industrial salt. This study aimed to determine the effects of liquid organic fertilizer Gracilaria sp. addition into the culture media of Tetraselmis chuii on Artemia sp. growth, to identify the profile of length, weight, and survival rate of Artemia sp., and finally attempted to uncover the contribution of Artemia sp. in impurity mineral absorption and NaCl content improvement. The results of the study showed that the density of T. chuii based on the concentration of liquid organic fertilizer Gracilaria sp. was significantly different (p<0.05) in each treatment. T. chuii cultivation using liquid organic fertilizer Gracilaria sp. 16 mg N/mL resulted in the highest density on the culture days. However, the studies showed that there was no significant effect (p>0.05) on the weight and length gain of Artemia sp. The research conducted can support the downstream use of products from engineering research in the field of technology to increase the added value of salt products and be part of the contribution to the achievement of the 14th SDG on life below water. Highlight Research Integration of chuii and Artemia sp. culture in salt production could improve NaCl contents by up to 97% and reduced impurities of sulfate and magnesium. The result of the first phase of this study is the density of chuii. This finding is useful to find out the effects of Gracilaria sp. liquid organic fertilizer administration as a source of nitrogen that improves the growth of T. chuii. The highest density of T. chuii resulted from a treatment receiving the dose of 16 N mg/L Gracilaria sp. liquid organic fertilizer with > 5 x 106 cells/mL. This finding indicates that the administration of 16 N mg/L Gracilaria liquid organic fertilizer into the culture medium provided a source of nitrogen and phosphorus for the metabolism of T. chuii. The results of the mineral content test on Artemia sp. show the largest percentage change in Mg2+ > SO42- > Cl- > Na+. The densities of Artemia sp. showed a positive trend of increasing levels of Mg2+ and SO42-, which coincided with decreasing levels of Mg2+ and SO42- in seawater media. The results of NaCl content measurement in water with Artemia sp. culture integration show salt with excellent quality of 97% that met the criteria of industrial salt. The contribution of Artemia sp. to improving the quality of salt products is interesting and has the potential to serve as an alternative to the traditional salt-farming system that is currently practiced.